The grammarians [compact disc, unabridged] - Schine, Cathleen (Macmillan Audio, 2019)
Laurel and Daphne Wolfe are identical, inseparable redheaded twins who share an obsession with words. They speak a secret 'twin' tongue of their own as toddlers; as adults making their way in 1980s Manhattan, their verbal infatuation continues, but this love, which has always bound them together, begins instead to push them apart. Daphne, copy editor and grammar columnist, devotes herself to preserving the dignity and elegance of Standard English. Laurel, who gives up teaching kindergarten to write poetry, is drawn, instead, to the polymorphous, chameleon nature of the written and spoken word. Their fraying twinship finally shreds completely when the sisters go to war. absurdly but passionately, over custody of their most prized family heirloom; Merriam Webster's New International Dictionary; Second Edition.